Competence of Junior high Schools' Science Teachers in Implementing Laboratory Teaching: A Case Study on Palu, Centre Celebes - Supriyatman Supriyatman; Amiruddin Kade; I Wayan Darmadi; Miftah Miftah; Supriyadi Supriyadi; Ismail Ismail (Jurnal Penelitian Pendidikan IPA, 2024)
This research investigates the competence of junior high school science teachers in Palu City, Indonesia, regarding laboratory teaching. The study aims to assess teachers' abilities in planning, implementing, and evaluating laboratory-based learning. Data were collected through observations, document reviews, and interviews with science teachers across six public junior high schools. The findings reveal that all schools engage in laboratory learning to some extent, with varying degrees of success. Teachers often create their own worksheets or use existing guides from science kits. Challenges identified include insufficient laboratory space, incomplete equipment, and a lack of dedicated laboratory assistants. Despite these obstacles, science teachers collaborate to ensure effective laboratory learning, highlighting the need for improved resources and support to enhance the overall quality of science education. The study concludes that while teachers demonstrate competency in laboratory teaching, further development is needed in creating practicum guides, conducting experiments, and assessing student skills. Future research should explore the impact of teacher competence on student learning outcomes in laboratory settings.